Layanan Bimbingan Kelompok Dengan Teknik Cognitive Therapy dalam Meningkatkan Efikasi Diri pada Siswa - Dwi Agustia Kurnianingsih; Nurussakinah Daulay (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to examine the effect of group counseling services using the cognitive therapy technique on improving students’ self-efficacy at MTs Negeri Pematangsiantar. The research was motivated by initial findings that several students had low self-efficacy levels, which negatively impacted their learning motivation. This quantitative research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of 16 eighth-grade students with low self-efficacy, divided into an experimental group (8 students) and a control group (8 students), selected using purposive sampling. Data were collected using a self-efficacy scale with a reliability coefficient of α = 0.975. Data analysis used the Mann-Whitney test. The results revealed a significant difference between the post-test scores of the experimental and control groups (Asymp. Sig. = 0.005 < 0.05). The experimental group’s mean score increased from 39.375 (low category) to 53.5 (moderate category), while the control group only increased from 40.143 to 44.143 (remaining in the low category). These findings indicate that group counseling services using cognitive therapy are effective in enhancing students’ self-efficacy. The study recommends that school counselors apply this technique sustainably to help students develop positive thinking patterns, increase motivation, and strengthen confidence in facing academic and personal challenges.